Quantitative analysis of Borrelia burgdorferi gene expression in naturally (tick) infected mouse strains - Lederer, Sharon; Brenner, Christiane; Stehle, Thomas; Gern, Lise; Wallich, Reinhard; Simon, Markus M. (Medical microbiology and immunology, 2005)
Adaptation of Borrelia burgdorferi in the vector and vertebrate host is mediated by mechanisms that regulate differential expression of outer surface lipoproteins (Osps). In this study, real time PCR was applied to quantify tissue-specific expression of four linear plasmid (lp54)-encoded (ospA, zs7.a36, zs7.a66 zs7.a68) and one circular plasmid (cp26)-encoded (ospC) gene from B. burgdorferi sensu stricto, in a natural setting of tick-infected immunodeficient (C.B-17 SCID) and immunocompetent (BALB/c and AKR/OlaHsd) mice for up to 120 days post-infection (p.i.). Early during infection (day 30 p.i.) high numbers of spirochetes were found in the heart and joint, but not the ear and spleen tissues of disease-susceptible SCID mice. In disease-susceptible AKR mice spirochetes colonized the ear and joint tissues, but were undetectable in tissues of disease-resistant BALB/c mice. Later in infection (day 120 p.i.), spirochetes had expanded (approximately 1,000-fold) in all SCID tissues tested but were undetectable in AKR and BALB/c mice. Of the five genes analyzed, only zs7.a36 transcripts were detected in various tissues of all infected mouse strains, though at differing levels, whereas ospC transcripts were only found in tissue specimens of SCID mice. Furthermore, gene expression of ospC and zs7.a36 appears to be differentially regulated in distinct organs of individual mice. In contrast, transcripts for ospA, zs7.a66, and zs7.a68 were not detected in any of the mouse strains, independent of their immune status and/or the severity of their infection/inflammatory responses. Late during infection (day 120 p.i.), transcription of zs7.a36 and ospC was down-regulated in the tissues of SCID mice despite expansion of spirochetes. This type of quantitative analysis may be helpful to further disclose principles of pathogenesis of Lyme borreliosis and to design strategies for its therapeutic treatment.